Pengaruh Jenis Pekerjaan, Alat Pelindung Diri Dan Riwayat Atopi Tehadap Dermatitis Kontak Iritan Pada Petugas Cleaning Service - Pravitasari, Dwi Nurwulan; Nurainiwati, Sri Adila; Armyati, Eky Okviana; Devi, Raihan Fatihka (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
Â Cleaning service (CS) is a job that often causes irritant contact dermatitis due to frequent contact with materials in the work environment, where the work is wet and is associated with water, soap, or other chemicals in a moment or repeatedly. This study aims to determine the effect of type of work, use of personal protective equipment, and history of atopy on the incidence of irritant contact dermatitis in cleaning service employees at the University of Muhammadiyah Malang. This study used an analytic observational method with a cross-sectional approach. The entire CS of the University of Muhammadiyah Malang population is 42 people with simple random sampling. The research data used a questionnaire from the British Health and Safety Executive (HSE UK) with the analysis technique using the Fisher Exact and Kruskal Wallis tests (alternative chi-square) in the bivariate test. In contrast, for multivariate, it used logistic regression. The research results obtained included: (1) bivariate, there was a relationship between the type of work (p=0.017), the use of personal protective equipment (p=0.047), and a history of atopy (p=0.001) in CS employees at the University of Muhammadiyah Malang. Furthermore, multivariate, there is a significant effect between the type of work (sig Wald = 0.029), use of personal protective equipment (sig Wald = 0.032), and history of atopy (sig Wald = 0.013). In conclusion, irritant contact dermatitis has a significant relationship with the type of work, use of PPE, and history of atopy.